Deployment of windows update using KiXtart scripting language / Izan Baizura Mohd Ismail - Mohd Ismail, Izan Baizura (Faculty of Information Technology and Quantitative Sciences, 2006)
System administrators no longer have the luxury of applying system patches when time permits. Worm and virus writers have taken advantage of many new technologies that allow them to reverse engineer system vulnerabilities and release them to the public. To maintain a certain level of security, network administrator has to check whether the entire client in the network has an updated version of the patch. System administrator has to keep up-to-date with the patches released by Microsoft to secure their network from being compromised. Failing to do so can make the network vulnerable to attacks. By using script to check for the pending updates can gives the system administrator two benefits, checking if the patch is critical to their system by first reading the feedback on the Internet and know which machine that needed to be patched. A simple script can ease the process of deploying the patches to the client in the network. This can make the system administrator works a lot easier and take the trouble off theirs minds.